COLORING r-DYNAMIC POINT ON CRICKET GRAPH - Kusumawati, Nurita; Kristiana, Arika Indah; Alfarisi, Ridho; Adawiyah, Robiatul; Setiawan, Toto Bara; Prihandini, Rafiantika Megahnia (JURNAL DIFERENSIAL, 2024)
A graph is defined as an ordered set (V,E) where V is a non-empty set of elements called vertices and E is a set of edges which are finite and may be empty and each edge connects two different points of V(G).The r-dynamic coloring is defined as c:V(G)→{1,2,3,…,k} such that it satisfies the following conditions if uv∈V(G), then c(u)≠ c(v), and ∀v∈V(G), |c(N(v))|≥min⁡{r,d(v)}, for positive integers r and degree of vertex v. The purpose of r-dynamic coloring is to find the minimum chromatic number of graph coloring with unlimited parameter r. Dynamic coloring is performed on cricket graphs because no research has been done before. The method used in this research is the axiomatic deductive research method and the pattern detection method.